From the Rondon to the Fritanga: Culinary References in the Poetry of Nicaragua - Villalobos, Carlos Manuel (2018)
This article studies the Nicaraguan cuisine as a recurring brand in the lyrical production of this country. Although there are some allusions to this issue in the context of modernist poetry, most references to the Nicaraguan menu are a recent stage, coinciding with the popularization of this genre, after the triumph of the Sandinista Revolution in 1979. Are considered for this study highlights the poem “Menu nica” by Luis Rocha, published in 1996 in his book La vida consciente, as well as texts by Carola Brantone, Esthela Calderón, Blanca Castellón, Edgar Escobar, Roger Fisher and Carlos Perezalonso, among other authors. One of the relevant discoveries of this work is the realization that in Nicaraguan Caribbean poetry, cooking is a priority theme, especially as a strategy to represent the values of regional identity. Thanks to this culinary reference in poetry, it is possible to determine how the syntagmatic and semiotic codes of the Nicaraguan table are constituted.